Alternative Polyadenylation Utilization Results in Ribosome Assembly and mRNA Translation Deficiencies in a Model for Muscle Aging. Issue 6 (4th March 2022) - Mei, Hailiang; Boom, Jasper; el Abdellaoui, Salma; Abdelmohsen, Kotb; Munk, Rachel; Martindale, Jennifer L; Kloet, Susan; Kielbasa, Szymone M; Sharp, Thomas H; Gorospe, Myriam; Raz, Vered
Abstract: Aging-associated muscle wasting is regulated by multiple molecular processes, whereby aberrant mRNA processing regulation induces muscle wasting. The poly(A)-binding protein nuclear 1 (PABPN1) regulates polyadenylation site (PAS) utilization, in the absence of PABPN1 the alternative polyadenylation (APA) is utilized. Reduced PABPN1 levels induce muscle wasting where the expression of cellular processes regulating protein homeostasis, the ubiquitin-proteasome system, and translation, are robustly dysregulated. Translation is affected by mRNA levels, but PABPN1 impact on translation is not fully understood. Here we show that a persistent reduction in PABPN1 levels led to a significant loss of translation efficiency. RNA-sequencing of rRNA-depleted libraries from polysome traces revealed reduced mRNA abundance across ribosomal fractions, as well as reduced levels of small RNAs. We show that the abundance of translated mRNAs in the polysomes correlated with PAS switches at the 3′-UTR. Those mRNAs are enriched in cellular processes that are essential for proper muscle function. This study suggests that the effect of PABPN1 on translation efficiency impacts protein homeostasis in aging-associated muscle atrophy.